Calculation of the Technological Scheme of Traffic Control of Mine Transport in Open Mines - Djaksimuratov Karamatdin Mustapaevich; Maulenov Nurlibek Axmet o‘g‘li; Joldasbayeva Aysulu Baxitbay qizi; O‘telbayev Azizbek Alisher o‘g‘li; Kulmuratova Aliya Janabay qizi (Research Parks Publishing LLC, 2022)
Transport of overburden and mineral raw materials in surface mining is one of the most complex and costly processes today. Good transport roads are essential for successful transportation by trucks in open pit mines. Poor design, and maintenance of the roads has the greatest impact on the high transport costs and possible risks in terms of security. Numerical modeling was performed to analyze the effects of the properties of the built-in materials used in the construction of roads, the thickness of the layers and the interaction of tires with the road surface. The distribution of stress and strain determined in the construction of a road depends on the characteristics of the road and the structure and mass of the truck. For this reason, numerical modeling and computer simulation is considered a very suitable method in the design of roads, because in a short period of time and at a lower cost calculations for the construction of a large number of models can be implemented and the best model available will be chosen. The most favorable construction will be considered to be the one that will, at minimum construction costs and with low costs of maintenance, enable the efficient use of transport equipment for a longer period of exploitation.